PATIENT SAFETY CULTURE: PERCEPTION OF NURSES IN A CARDIOPNEUMOLOGY REFERENCE CENTER - Ribeiro,Ana Carolina (2019)
ABSTRACT Objective: to evaluate the patient safety culture dimensions from the nurses' point of view in a cardiopneumology reference hospital in the city of São Paulo (Brazil). Method: a quantitative, descriptive-exploratory study. Nurses from Inpatient Units and intensive care units participated in this study, which responded to the Hospital Survey on Patient Safety Culture instrument, validated for Brazil. Data was collected from July to September 2017. For data analysis, descriptive and inferential statistics were used; percentages greater than or equal to 75% of positive responses represent satisfactory results regarding to the patient safety culture. Results: of 102 nurses, 52 (51%) worked in inpatient units and 50 (49%) in intensive care units, 90.2% being nursing assistants. Females predominated (85.3%) and the mean age was 37.5 years old. As for the safety culture, the best rated dimension was “Organizational Learning - Continuous Improvement” (59.4%) and the worst, “Nonpunitive Response to Errors” (24.1%). The best evaluations were from inpatient unit’s nurses, regarding items of positive answers at the hospital level (p=0.01), and negative answers at the level of the professional’s unit of work (p=0.04). Conclusion: these findings make it possible to draw up intervention plans to strengthen and solidify components that encompass safety culture in the institution on this research scenario.